2006
DOI: 10.1016/j.rmedu.2006.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in household stoves and risk of chronic obstructive pulmonary disease in Xuanwei, China: Retrospective cohort study

Abstract: Objective To test whether improvement in household coal stoves affected the incidence of chronic obstructive pulmonary disease (COPD) in Xuanwei County, China. Design Retrospective cohort study (follow-up 1976-92) comparing incidence of COPD between groups with and without chimneys. Participants 20 453 people born into homes with unvented coal stoves;16 606 (81.2%) subsequently changed to stoves with chimneys. Intervention Installation of a chimney in households in which unvented stoves had been used previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These associations may be explained by the fact that COPD causes a long-standing inflammatory reaction in the bronchi and inflammation itself may play a role in the development of lung cancer (Balkwill and Mantovani, 2001;Littman et al, 2004;Mantovani, 2007). As several studies found that the mixture of pollutants from combustion of coal and biomass were associated with lung cancer as well as several other lung diseases, including COPD and PT (Smith et al, 2004;Chapman et al, 2005), all the ORs for lung cancer according to a history of lung diseases were also adjusted for exposure to IAP index, and the results did not substantially change, supporting an independent role of COPD and PT in lung carcinogenesis. Furthermore, the combination of exposure to IAP and COPD/TP led to an approximately sixfold increased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…These associations may be explained by the fact that COPD causes a long-standing inflammatory reaction in the bronchi and inflammation itself may play a role in the development of lung cancer (Balkwill and Mantovani, 2001;Littman et al, 2004;Mantovani, 2007). As several studies found that the mixture of pollutants from combustion of coal and biomass were associated with lung cancer as well as several other lung diseases, including COPD and PT (Smith et al, 2004;Chapman et al, 2005), all the ORs for lung cancer according to a history of lung diseases were also adjusted for exposure to IAP index, and the results did not substantially change, supporting an independent role of COPD and PT in lung carcinogenesis. Furthermore, the combination of exposure to IAP and COPD/TP led to an approximately sixfold increased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…71 Chronic exposure has been linked with the development of chronic obstructive pulmonary disease 73 and emphysema. 74 …”
Section: Biomass Fuelsmentioning
confidence: 99%